Sperm DNA fragmentation index: limited effectiveness on predicting embryo quality in assisted reproduction technology treatments - Huan Jiang; Xiaolu Xia; Ying Luo; Haiyan Pan; Shihao Qu; Jianying Xu (Reproductive Biology and Endocrinology)
Abstract Purpose Prior sperm DNA fragmentation index (DFI) thresholds for diagnosing male infertility and predicting assisted reproduction technology (ART) outcomes fluctuated between 15 and 30%, with no agreed standard. This study aimed to evaluate the impact of the sperm DFI on early embryonic development during ART treatments and establish appropriate DFI cut-off values. Methods Retrospectively analyzed 913 couple’s ART cycles from 2021 to 2022, encompassing 1,476 IVF and 295 ICSI cycles, following strict criteria. The WHO guidelines directed the semen analysis, while the acridine orange test (AOT) determined the DFI. Male factors (age, BMI, DFI, infertility duration, sperm parameters) and female parameters (age, BMI, AMH, retrieved oocytes) were evaluated. We also assessed embryological parameters like fertilization rate, cleavage rate, and blastocyst quality. Correlations between DFI and embryo quality were examined and DFI cut-off values were established using ROC analysis. Results The Sperm DFI demonstrated a positive correlation with male age and a negative correlation with sperm motility, concentration, and normal morphology, while showing no relation to BMI. No connection between DFI and embryological parameters in only IVF and ICSI groups was found, but a negative correlation with fertilization rate was seen in all ART cycles. ROC curve analysis revealed a DFI cut-off value of 21.15% having 36.7% sensitivity and 28.9% specificity in predicting high fertilization rate (≥ 80%). Conclusion Sperm DFI had a negative correlation with fertilization rate, but limited predictive efficacy and no significant link to other embryological parameters. DFI assessments may improve early embryo development prediction during ART treatments, particularly in older males or those exhibiting poor sperm quality.